Characterization of del20q in Peripheral Blood of MPD Patients Using Copy Number Analysis and High Resolution Oligonucleotide CGH Array - Schaub, Franz; Tiedt, Ralph; Hermouet, Sylvie; Girodon, François; Kralovics, Robert; Tichelli, André; Skoda, Radek C. (Blood, 2007)
Previous studies showed that deletions of the long arm of chromosome 20 (del20q) are the most common chromosomal aberration in myeloproliferative disorders (MPD) and can be found in up to 10% of patients with polycythemia vera (PV). We screened 447 MPD patients (177 PV, 228 essential thrombocythemia (ET), 42 primary myelofibrosis (PMF)) for loss of gene copy number in the del20q region. Granulocyte DNA was assayed using a quantitative PCR assay for two different exons of the L3MBTL gene, which is located in the common deleted region. Since deletions can only be detected if the majority of granulocytes have lost a copy of L3MBTL, this method selects for del20q events that provided a selective advantage for the clone. Samples that showed a decrease in copy number in the initial screen were validated using primers in neighbouring genes. We found del20q in peripheral blood of 29/447 patients (6%), including 9/177 PV (5%), 12/228 ET (5%), and 8/42 PMF (19%). The observed frequency of del20q in peripheral blood is lower than reported in previous studies for bone marrow analysis. The patients positive for del20q in this screen were chosen for mapping of the deleted region by high density oligonucleotide comparative genomic hybridisation (CGH) array. A custom chip was designed with 94'000 probes from chromosome 20q, with an average resolution of 500bp. We have so far analyzed 6 patients and confirmed del20q by CGH in all of them. The deleted regions in these patients overlapped with the published common deleted region. We will use CGH to map the remaining 23 patients. Since the majority of the del20q positive patients also carried the Jak2-V617F mutation, we performed clonogenic assays and analyzed single colonies. In one patient all 94 colonies were double positive for del20q and JAK2-V617F. In a second patient 54 colonies were double positive and 10 colonies only carried del20q, but not JAK2-V617F, indicating that del20q occurred before the acquisition of JAK2-V617F.